Simplified Assessment of the Index of Microvascular Resistance. (2nd June 2021) - Kodeboina, Monika; Nagumo, Sakura; Munhoz, Daniel; Sonck, Jeroen; Mileva, Niya; Gallinoro, Emanuele; Candreva, Alessandro; Mizukami, Takuya; Van Durme, Frederik; Heyse, Alex; Wyffels, Eric; Vanderheyden, Marc; et al.
Abstract : Background . To validate a simplified invasive method for the calculation of the index of microvascular resistance (IMR). Methods . This is a prospective, single-center study of patients with chronic coronary syndromes presenting with nonobstructive coronary artery disease. IMR was obtained using both intravenous (IV) adenosine and intracoronary (IC) papaverine. Each IMR measurement was obtained in duplicate. The primary objective was the agreement between IMR acquired using adenosine and papaverine. Secondary objectives include reproducibility of IMR and time required for the IMR measurement. Results . One hundred and sixteen IMR measurements were performed in 29 patients. The mean age was 68.8 ± 7.24 years, and 27.6% was diabetics. IMR values were similar between papaverine and adenosine (17.7 ± 7.26 and 20.1 ± 8.6, p = 0.25 ; Passing-Bablok coefficient A 0.58, 95% CI −2.42 to 3.53; coefficient B 0.90, 95% CI −0.74 to 1.07). The reproducibility of IMR was excellent with both adenosine and papaverine (ICC 0.78, 95% CI 0.63 to 0.88 and ICC 0.93, 95% CI 0.87 to 0.97). The time needed for microvascular assessment was significantly shortened by the use of IC papaverine (3.23 (2.84, 3.78) mins vs. 5.48 (4.94, 7.09) mins, p < 0.0001 ). Conclusion . IMR can be reliably measured using IC papaverine with similar results compared to intravenous infusion of adenosine with increased reproducibility and reduced procedural time. This approach simplifies the invasive assessment of the coronary microcirculation in the catheterization laboratory.